By failing to prepare, you are preparing your anterior cruciate ligament to fail - Staynor, J. M. D.; Alderson, J. A.; Byrne, S.; Rossi, M.; Donnelly, C. J. (Scandinavian Journal of Medicine & Science in Sports, 2020)
There is strong evidence linking an athlete's movement technique during sidestepping with anterior cruciate ligament (ACL) injury risk. However, it is unclear how these injurious postures are influenced by prior movement. We aim to describe preparatory trunk and thigh kinematics at toe-off of the penultimate-step and flight-phase angular momenta, and explore their associations with frontal-plane risk factors during unplanned sidestepping maneuvers. We analyzed kinematic and kinetic data of 33 male Australian Football players performing unplanned sidestepping tasks (103 trials). Linear mixed models tested for reliable associations between ACL injury risk during weight acceptance of the execution-step, with preparatory kinematics and angular momenta of the trunk and thigh during the penultimate-step. Multi-planar flight-phase trunk momenta along with hip abduction angle at penultimate-step toe-off were significantly associated with peak knee valgus moments during the execution-step (R2 = .21, P < .01). Execution-step trunk lateral flexion was significantly predicted by frontal and sagittal-plane preparatory trunk positioning at toe-off of the penultimate-step (R2 = .44, P < .01). Multi-planar flight-phase trunk momenta as well as multi-planar trunk and hip positioning at penultimate-step toe-off were associated with hip abduction during the execution-step (R2 = .53, P < .01). Preparatory positioning of the trunk and hip, along with flight-phase trunk momentum adjusting this positioning are linked to known ACL injury risk factors. We recommend that during the penultimate-step athletes maintain an upright trunk, as well as minimize frontal-plane trunk momentum and transverse-plane trunk momentum toward the sidestep direction to reduce risk of ACL injury during unplanned sidesteps.